Energy-efficient H∞ filtering for networked systems with stochastic signal transmissions - Zhang, Dan (2016)
This paper is concerned with the energy-efficient filtering for a class of wireless sensor networks (WSNs). Due to the power limitation of WSNs, the measurement signal is transmitted to the remote filter infrequently and stochastically. A stochastic framework is proposed to formulate the filtering problem for such systems. A sufficient condition is established such that the filtering error system is mean-square stable and achieves a prescribed disturbance attenuation level in the H∞ sense. The optimal filter design is presented to determine the filter gains. Relations between the transmission parameters, e.g., transmission probability, transmission intervals and the filtering performance are obtained. Finally, a continuous stirred tank reactor (CSTR) system is employed to evaluate the effectiveness of the proposed design.